Socio-environmental vulnerability, agrochemicals and impacts on health in the southern coastal and peri-urban corridor of Mar del Plata (Buenos Aires, Argentina) - Molpeceres, María Celeste (2023)
In line with the global trends, Argentine agriculture has been characterized in recent decades by its accelerated intensification processes. This fact is especially linked to the so-called technological package, derived from the Green Revolution, which is linked to technological, chemical and mechanical proposals highly dependent on inputs such as oil. On the other hand, this approach implies a high environmental and social cost. This condition is especially verified in the Argentine Pampean region, in which, the General Pueyrredon municipality (GPM) has been the scene of tensions and controversies related to the use of agrochemicals for more than two decades. This study evaluates the socio-environmental vulnerability of the population exposed to agrochemicals in the southern coastal and peri-urban corridor of Mar del Plata (GPM), Buenos Aires Province, Argentina in order to discuss possible health risks and their approach by local management. For this purpose, a socio-environmental vulnerability index (IVSA) was constructed, which accounts for the population’s capacity to prevent, reduce or face the risks associated with such exposure. The spatial distribution of the IVSA and its indicators were analyzed through a Geographic Information System and the most critical areas were identified. The results reveal better conditions of the IVSA in coastal areas close to the urban common land, where the infrastructure of basic sanitation services has a favorable impact. This work, together with the monitoring of health conditions, constitutes an input for the design of planning policies in pursuit of sustainable development in the area.